The sources of social power, Volume 3, Global empires and revolution, 1890-1945 - Mann, Michael 1942- (Cambridge University Press, 2012)
Distinguishing four sources of power - ideological, economic, military and political - this series traces their interrelations throughout human history. This third volume of Michael Mann's analytical history of social power begins with nineteenth-century global empires and continues with a global history of the twentieth century up to 1945. Mann focuses on the interrelated development of capitalism, nation-states and empires. Volume 3 discusses the 'Great Divergence' between the fortunes of the West and the rest of the world; the self-destruction of European and Japanese power in two world wars; the Great Depression; the rise of American and Soviet power; the rivalry between capitalism, socialism and fascism; and the triumph of a reformed and democratic capitalism